Assessment of knowledge and attitudes regarding obstructive sleep apnea among interns, residents and medical doctors of Kathmandu Medical College - Shrestha, Inku; Shrestha, Diva; Bista, Raunak; Bista, Meera (Journal of Chitwan Medical College, 2021)
Background: Obstructive sleep apnea (OSA) is a global health problem observed mostly among children and adults resulting in poor quality of life and increased cost of health care. Medical doctors should be familiar with OSA and be able to screen, diagnose and manage this condition. This study was aimed to assess the knowledge and attitudes regarding Obstructive Sleep Apnea among interns, residents and medical doctors of Kathmandu Medial College. Methods: A descriptive cross-sectional study was conducted among interns, residents and medical doctors of Kathmandu Medial College. The study was conducted from September 2021 to October 2021.The previously validated Obstructive Sleep Apnea Knowledge and Attitudes (OSAKA) questionnaire was administered to the participants. The data obtained from the study was analyzed using descriptive statistics with SPSS 21. Results: Among the study respondents, females comprised of 105 (55 %) and rest were males. Almost 178 (93.2%) of participants were aware of snoring habits of majority of OSA patients, while 173 (90.6%) of respondents knew that the large tonsils and adenoids was the most common cause of OSA in children. Majority of the respondents agreed on OSA as a clinical disorder and that it was important to be able to identify patients with possible OSA. More than half of the respondents felt confident to identify patients at risk for OSA. Conclusions: This study showed that the participants lack adequate knowledge. However, they agreed that OSA is a clinical disorder. They need to update the knowledge about OSA. There is also a need of special training programs on OSA.